The Influence of The Teacher’s Example on The Morals of 4th Grade Students Islamic Teacher Training College at Darussalam Modern Islamic Boarding School - Noor Syahid; M. Makruf Al Arif (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
The Islamic Teacher Training College at the Darussalam Gontor Modern Islamic Boarding School is famous with Five Spirits, Five Termes, and its Mottoes. One of its mottoes is Noble Character. Noble Character is the most important foundation which is instilled by the cottage to all its students at all levels and all education and teaching must contain character. Exemplary teacher is a figure that must be followed by all students and the teacher has become an example not just giving an example to students. So if the teacher is good, the students are good. And able to apply it in their daily lives. However, there are some 4th grade students of KMI who have not been able and have noble morals both for God, for humans and for themselves. As a result, many of them violated discipline. In fact, the higher the class, the lower the character. The purpose of this research was to determine: 1) The exemplary teachers of KMI at Darussalam Gontor Modern Islamic Boarding School. 2) Character traits of students of class 4 KMI Darussalam Gontor Modern Islamic Boarding School. 3) Knowing whether or not there is an influence of the teacher's example on the morals of students in class 4 KMI Darussalam Gontor Modern Islamic Boarding School on period 1440-1441.The type of research that the researcher took is the quantitative and quantitative field research (Quantitatif). The population of class 4 KMI students is 430 with a sample taking of 23% totaling 99 students by random method. Data collection techniques used were: (1) Questionnaire, to determine the exemplary teachers of KMI and the Characters of students of class 4 KMI Darussalam Gontor Modern Islamic Boarding School. (2) Documentation, to obtain data about the general picture of the cottage. The data analysis uses the product moment correlation technique with a significance level of 5%.The results of this research are: 1) The exemplary teachers of KMI Darussalam Gontor Modern Islamic Boarding School in the 1440-1441 H school year reached an average value of 122.68 with a very high degree. 2) Moral Character of students in class 4 KMI Darussalam Gontor Modern Islamic Boarding School in the academic year 1440-1441 H reached an average value of 105.26 with a high degree. 3) There is a strong influence with a value of 0,379 0r 37,9 % and the Significance 0,000<0,05 between the exemplary teachers of KMI and the morals of students of the class 4 KMI Darussalam Gontor Modern Islamic Boarding School on period 1440-1441.